Conceptualisation of the characteristics of advanced practitioners in the medical radiation professions - Smith, Tony (J Med Radiat Sci, 2015)
Professions grapple with defining advanced practice and the characteristics of advanced practitioners. In nursing and allied health, advanced practice has been defined as ‘a state of professional maturity in which the individual demonstrates a level of integrated knowledge, skill and competence that challenges the accepted boundaries of practice and pioneers new developments in health care’. Evolution of advanced practice in Australia has been slower than in the United Kingdom, mainly due to differences in demography, the health system and industrial relations. This article describes a conceptual model of advanced practitioner characteristics in the medical radiation professions, taking into account experiences in other countries and professions. Using the CanMEDS framework, the model includes foundation characteristics of communication, collaboration and professionalism, which are fundamental to advanced clinical practice. Gateway characteristics are: clinical expertise, with high level competency in a particular area of clinical practice; scholarship and teaching, including a masters qualification and knowledge dissemination through educating others; and evidence-based practice, with judgements made on the basis of research findings, including research by the advanced practitioner. The pinnacle of advanced practice is clinical leadership, where the practitioner has a central role in the health care team, with the capacity to influence decision making and advocate for others, including patients. The proposed conceptual model is robust yet adaptable in defining generic characteristics of advanced practitioners, no matter their clinical specialty. The advanced practice roles that evolve to meet future health service demand must focus on the needs of patients, local populations and communities.